What Rate of Return Can You "Reasonably" Expect? - Bernstein, Peter L. (Journal of Finance, 1973)
Peter L. Bernstein, What Rate of Return Can You "Reasonably" Expect?, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 273-282